Type I tympanoplasty in children: Our results - Pinto, Ana Nóbrega (2017)
Objectives: To evaluate the type I tympanoplasty results in children and to analyze some factors referred as potential determinants in their success.Study Design: Observational, analytical and retrospective studyMaterial and Methods: Analysis of 22 clinical cases of pediatric patients (<18 years) undergoing primary type I tympanoplasty in Centro Hospitalar do Porto, between 01/01/2013 and 01/31/2014. We collected and analyzed individual variables and determined of the corresponding anatomical and functional success rate.Results: An anatomical success rate of 73% and functional success of 82% was obtained (mean follow-up: 16.77 ± 07.11 months). Success rates were not significantly different between the two age groups analyzed. The lowest anatomical success rate in larger perforations was statistically significant.Conclusions: The success rates obtained are consistent with the results described in the literature. In this study the only variable related to anatomic and functional failure was the size of the perforation.